2022
DOI: 10.1155/2022/5952450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dielectric and Magnetic Nanoparticles on the Electrical, Mechanical, and Thermal Properties of Unidirectional Carbon Fiber-Reinforced Composites

Abstract: Carbon fiber-reinforced particulate composites are immensely used in commercial and military applications due to their excellent functional and mechanical performance. Several studies have been reported to use nanofiller in carbon fiber-reinforced composites to improve their functional and mechanical performance. However, a comparative study was required to depict the best dielectric and magnetic nanofillers with excellent functional and mechanical performance. The current research was performed to compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…When the chemical etching process was achieved after peel ply removal, it removed the contaminants of the peel ply, cleaned the composite substrate, and added micro-roughness to the composite substrate surface ( Figure 7 b). The additional process after peel ply treatment etched the surface homogeneously at the microlevel (without disturbing bulk properties) [ 18 ]. This allowed for an improvement in the contact area and interlocking points between the adhesive and composite substrate surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the chemical etching process was achieved after peel ply removal, it removed the contaminants of the peel ply, cleaned the composite substrate, and added micro-roughness to the composite substrate surface ( Figure 7 b). The additional process after peel ply treatment etched the surface homogeneously at the microlevel (without disturbing bulk properties) [ 18 ]. This allowed for an improvement in the contact area and interlocking points between the adhesive and composite substrate surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both will perform best in different temperature ranges. Ultimately, adhesive joints developed using these adhesives will have different temperature stabilities [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…These PNCs are synthesized when nanosized particles of various shapes and sizes are reinforced into a polymer matrix [ 5 ]. However, the reinforcing impact of these nanoparticles is highly dependent on the aspect ratio, size, orientation and dispersion [ 6 ]. The reinforcement of these nanofillers ultimately enhances PNC’s mechanical, thermal, barrier and flammability properties without compromising their processability [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Raza et al 40 studied process‐induced deformations in glass/unsaturated polyester cross‐ply C‐shaped cylindrical structures and found that the value of diameter reduction was reduced from 6 to 3 mm by the addition of 5% silica particles. Ahmad et al 41 investigated the effect of different dielectric and magnetic nanoparticles on the electrical, mechanical, and thermal properties of carbon fiber‐reinforced composites. They found that the composite samples containing MWCNT nanofiller showed the highest electrical, thermal, and mechanical properties among the dielectric nanofillers, and the composite samples containing titanium oxide nanofillers showed better flexural, electrical, and thermal properties among magnetic nanofillers.…”
Section: Introductionmentioning
confidence: 99%